Case Report: Chronic hepatitis E virus Infection in an individual without evidence for immune deficiency - Ying, Dong; Niu, Wenxia; Chen, Yanling; Wang, Yingbin; Tian, Weikun; Zhang, Xiaoping; Liu, Chang; Wang, Siling; Chen, Zihao; Lin, Yajie; Guo, Shaoqi; Yu, Zihao; et al. (Frontiers in Immunology, 2023)
Chronic Hepatitis E virus (HEV) infection has only been reported in immunosuppressed populations. We describe an investigation of chronic HEV infection in an immunocompetent individual who presented hepatitis with significant HEV viremia and viral shedding. We monitored HEV RNA in plasma and stools, and assessed anti-HEV specific immune responses. The patient was immunocompetent based on quantified results of white blood cell, lymphocyte, neutrophilic granulocyte, CD3+ T cell, CD4+ T cell, and CD8+ T cell counts and CD4/CD8 ratio, as well as total serum IgG, IgM, and IgA, which were in the normal range. Despite HEV specific cellular response and strong humoral immunity being observed, viral shedding persisted up to 109 IU/mL. After treatment with ribavirin combined with interferon, the indicators of liver function in the patient returned to normal, accompanied by complete suppression and clearance of HEV. These results indicate that HEV chronicity can also occur in immunocompetent individuals.